2016
DOI: 10.1177/0333102415620252
|View full text |Cite
|
Sign up to set email alerts
|

SUNCT syndrome: A cohort of 15 Portuguese patients

Abstract: Our case series is among the largest reported, with findings similar to others already published, but the first to report epistaxis during SUNCT attack and response to eslicarbazepine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
2
8
1
Order By: Relevance
“…Conversely, although CBZ and OXC are routinely used for the treatment of neuropathic pain, ESL has scarcely been explored in this area (Alcántara Montero and Sánchez Carnerero, ). A Spanish group (Garcia‐Escrivà et al., ) studied ESL for the treatment of painful diabetic neuropathy; furthermore, a Portuguese study reported a positive response to ESL in a case of short‐lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) (Cação et al., ). Currently, there are no studies that evaluate ESL for the treatment of TN in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, although CBZ and OXC are routinely used for the treatment of neuropathic pain, ESL has scarcely been explored in this area (Alcántara Montero and Sánchez Carnerero, ). A Spanish group (Garcia‐Escrivà et al., ) studied ESL for the treatment of painful diabetic neuropathy; furthermore, a Portuguese study reported a positive response to ESL in a case of short‐lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) (Cação et al., ). Currently, there are no studies that evaluate ESL for the treatment of TN in humans.…”
Section: Introductionmentioning
confidence: 99%
“…A refractory period was absent in the vast majority of patients. Cacao et al reported similar clinical findings except for a lower frequency of attacks and a possible lack of male preponderance. In very rare cases, pain may be extratrigeminal or bilateral .…”
Section: Sunct/sunamentioning
confidence: 65%
“…In only one patient, however, the neurovascular contact was exclusively ipsilateral to the pain. In the series by Cacao et al, MRI revealed “ipsilateral trigeminal neurovascular contact” in four of 15 patients. In three patients with neurovascular contact and a diagnosis of SUNCT, the authors described a preserved refractory period .…”
Section: Sunct/sunamentioning
confidence: 93%
See 2 more Smart Citations